Electromagnetic absorption materials: Current progress and new frontiers. (June 2022) - Lv, Hualiang; Yang, Zhihong; Pan, Hongge; Wu, Renbing
Abstract: The rapid development of wireless communications especially with the coming of 5G, and artificial intelligence (AI) provides us a wonderful and intelligent life. Nevertheless, it is at the expense of a substantial increase in electromagnetic (EM) inference and pollution. EM absorbing materials that can dissipate the incident EM waves are of crucial importance in solving EM pollution and thus have received significant attention. This article provides a comprehensive review of the current status and new frontiers on EM absorption materials. It begins with the fundamentals of EM apsorption materials, with an emphasis on their mechanisms and characterizations. Discussion is then made on the chemical strategies of component optimization and nanostructure engineering for developing traditional EM absorption materials. Thereafter, new advances particularly in next–generation EM materials including superhydrophobic, self–healing, high–temperature, optically manipulatable and electrically tuning EM absorbing materials as well as EM–electricity harvester are highlighted. Finally, this review is concluded with an outlook of future research on EM absorption materials, major challenges to be addressed and possible solutions.